2006
DOI: 10.1093/glycob/cwj096
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the enzyme complex regulating O-GlcNAcylation blocks signaling and development

Abstract: Although the knowledge that nuclear and cytoplasmic proteins are modified with N-acetylglucosamine has existed for decades, little has been shown as to its function until recently. There are now substantial data highlighting the significance of proper regulation of this modification in multiple cellular processes. Currently, only two enzymes are known that regulate this modification. O-GlcNAc transferase (OGT) modifies protein substrates posttranslationally by adding the N-acetylglucosamine. Bifunctional nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 45 publications
7
118
0
Order By: Relevance
“…Recently, Whisenhunt et al 31 showed by in vitro experiments that OGT forms a Among the HRT-responding genes we also found genes encoding both catabolic and anabolic agents. Androgen receptor (Ar) was significantly upregulated (13 %) in the HRT group.…”
supporting
confidence: 58%
“…Recently, Whisenhunt et al 31 showed by in vitro experiments that OGT forms a Among the HRT-responding genes we also found genes encoding both catabolic and anabolic agents. Androgen receptor (Ar) was significantly upregulated (13 %) in the HRT group.…”
supporting
confidence: 58%
“…The decrease in fertility is closely correlated to glucose concentration, suggesting that OGT-1 is acting as a nutrient sensor. O-GlcNAc cycling has also been implicated in the response to starvation, as OGT expression increases and OGA expression decreases in response to glucose deprivation (Kreppel et al 1997;Whisenhunt et al 2006), indicating that this pathway is finely tuned to maintain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Using high stringency reporter selection, we were able to identify 27 putative binding partners for OGT (Table 1). In our screen, two previously known interacting partners for OGT were successfully identified, namely O-GlcNAcase (25) and Trak1 (previously known as OIP106) (15). It is interesting to note that the proteins identified belong to a wide range of functional classes from ion transporting integral membrane proteins to signaling and transcriptional regulators.…”
Section: Putative Ogt-interacting Proteins Were Identified Using Amentioning
confidence: 94%